A de novo silencer causes elimination of MITF-M expression and profound hearing loss in pigs. Issue 1 (December 2016) - Chen, Lei; Guo, Weiwei; Ren, Lili; Yang, Mingyao; Zhao, Yaofeng; Guo, Zongyi; Yi, Haijin; Li, Mingzhou; Hu, Yiqing; Long, Xi; Sun, Boyuan; Li, Jinxiu; et al.
Abstract Background Genesis of novel gene regulatory modules is largely responsible for morphological and functional evolution. De novo generation of novelcis -regulatory elements (CREs) is much rarer than genomic events that alter existing CREs such as transposition, promoter switching or co-option. Only one case of de novo generation has been reported to date, in fish and without involvement of phenotype alteration. Yet, this event likely occurs in other animals and helps drive genetic/phenotypic variation. Results Using a porcine model of spontaneous hearing loss not previously characterized we performed gene mapping and mutation screening to determine the genetic foundation of the phenotype. We identified a mutation in the non-regulatory region of the melanocyte-specific promoter of microphthalmia-associated transcription factor (MITF ) gene that generated a novel silencer. The consequent elimination of expression of theMITF-M isoform led to early degeneration of the intermediate cells of the cochlear stria vascularis and profound hearing loss, as well as depigmentation, all of which resemble the typical phenotype of Waardenburg syndrome in humans. The mutation exclusively affectedMITF-M and no other isoforms. The essential function ofMitf-m in hearing development was further validated using a knock-out mouse model. Conclusions Elimination of theMITF-M isoform alone is sufficient to cause deafness and depigmentation. To our knowledge, this study provides the first evidence of a de novo CRE in mammals that produces a systemic functional effect.